2008
DOI: 10.1038/nmat2300
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling spectra of individual magnetic endofullerene molecules

Abstract: The manipulation of single magnetic molecules may enable new strategies for high-density information storage and quantum-state control. However, progress in these areas depends on developing techniques for addressing individual molecules and controlling their spin. Here, we report success in making electrical contact to individual magnetic N@C(60) molecules and measuring spin excitations in their electron tunnelling spectra. We verify that the molecules remain magnetic by observing a transition as a function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 39 publications
10
122
0
Order By: Relevance
“…N@C 60 [3]. As our ab-initio calculations explicitly demonstrate N@C 60 [3] possess indeed SAMOs that we may employ for magnetic pulse generation (cf. supplementary materials).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…N@C 60 [3]. As our ab-initio calculations explicitly demonstrate N@C 60 [3] possess indeed SAMOs that we may employ for magnetic pulse generation (cf. supplementary materials).…”
Section: Introductionsupporting
confidence: 53%
“…Here we exploit these properties of SAMOs for photo-generating surface charge current loops, and hence internal, nanoscale magnetic field pulses which act on encapsulated magnetic moments, e.g. N@C 60 [3]. As our ab-initio calculations explicitly demonstrate N@C 60 [3] possess indeed SAMOs that we may employ for magnetic pulse generation (cf.…”
Section: Introductionmentioning
confidence: 94%
“…2,5 Interestingly, at low temperatures these molecular junctions often exhibit Coulomb-blockade physics, which allows for a detailed analysis of spectroscopic features. For example, vibrational modes of the molecule 5,16 or magnetic excitations [17][18][19][20] have been probed for different charge states. In addition to these generic features, molecules tend to have symmetries that are usually accompanied with spectral degeneracies which in turn can give rise to certain instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Using such hybrid silicon-molecule transistor configuration, it was recently shown that it is possible to electrostatically modulate the current through the molecule by gating the molecular orbital with the underneath Si gate [154]. This hybrid silicon-molecule transistor configuration is also suitable to study and control the spin states and spin transport through molecules [151,[155][156][157][158].…”
Section: Molecular Transistorsmentioning
confidence: 99%